Time to achieving a designated criterion score level: A survival analysis study of test taker performance on the TOEFL iBT® test. (January 2021) - Monfils, Lora F.; Manna, Venessa F.
This study used survival analysis to examine the patterns and factors associated with time to achieving designated score criteria on a test of English as a foreign language. This was modeled using an extension of the Cox regression model, with two criterion score levels defined as achieving a TOEFL iBT® total test scale score at or above the Common European Framework of Reference (CEFR) Level B2 and at Level C1, respectively. Factors included in the model were test taker background characteristics including age, gender, native language type, exposure to English, and reason for testing. Additionally, to account for those who tested more than once within the study period, and thus had multiple records, an indicator for order of testing occasion was included in the model. Results indicate that approximately 82% of the test takers in our study sample tested one time in the study period (2014–2016), and the number of repeaters decreased rapidly across occasions. For those who did not achieve the designated criterion scores at first testing, the likelihood of achievement increases with repeated testing, with a somewhat greater effect for the less stringent B2 criterion. Results also indicate that the association of gender with performance differed across levels.